Traditional water installations and their tourism employment in Tunisia, the path of Hanaya water - from Zaghouan to Carthage as a model - - HANI, Fadel (Social Sciences Journal)
The problem of this research allows studying the role of traditional hydraulic techniques in the diversification of the tourist offer and the interest of cultural tourism for the conservation, valuation of this hydraulic heritage and realization of tourism development at the economic, social and cultural in the water circuit of Zaghouan to Carthage, which was created in the last years. This presidential project aims to revive the historical memory of the stream of Zaghouan to Carthage and the valuation of environmental and archaeological sites.In spite of the development of certain areas such as the temple of the water, the creation of a national park and an urban park in Zaghouan, the preservation of some historic monuments, the improvement infrastructure and accessibility of some sites, the tourism promotion in this circuit is insufficient. The circuit aqueduct is tourism of passage, in low impact on the local and regional development. The conservation of monuments is difficult and expensive.The development of ecotourism tourism in the circuit aqueduct requires consideration of ecological and economic dimensions and the preservation of cultural identity and interests of local communities for sustainable tourism development. The participation of the local populations in the valuation and development of this hydraulic heritage is necessary.